Antioxidant Activity of the Successive Extracts of Grewia asiatica Leaves - KUMAR GUPTA, MAHESH; LAGARKHA, REKHA; K. SHARMA, DHIRENDRA; SHARMA, P.K.; SINGH, RAMESH; ANSARI, H.S. (Asian Journal of Chemistry, 2010)
Plants containing flavonoids have been reported to possess biological properties. The successive extracts of Grewia asiatica leaves were screened for in vitro antioxidant properties using standard procedures. The successive extracts such as petroleum ether, benzene, ethyl acetate, methanol, water and 50 % crude methanol extracts exhibited IC50 values of 249.60 ± 7.37, 16.19 ± 2.132, 26.17 ± 1.49, 27.38 ± 1.80, 176.14 ± 5.53 and 56.40 ± 3.98 μg/mL, respectively in DPPH and 22.12 ± 02.65, 27.00 ± 01.62, 47.38 ± 05.88, 56.85 ± 06.16, 152.75 ± 5.76 and 72.75 ± 13.76 μg/mL, respectively in nitric oxide radical inhibition assays. These values are comparable with standards such as an ascorbic acid and quercetin. The Grewia asiatica leaves are showing antioxidant activity.